Towards a core outcome set for sarcopenia intervention studies: a scoping review identifying the most frequently reported outcomes across randomized controlled trials in sarcopenia - Van Heden, S.; Chan, Y. M.; Baoubbou, Z.; Bruyère, O.; Reginster, J. Y.; Surquin, M.; Sanchez-Rodriguez, D.; Beaudart, C. (Springer Science and Business Media Deutschland GmbH, 2025)
Aim: As a first step in the development of a Core Outcome Set, we carried out a scoping review using a systematic methodology to identify the most frequently reported outcomes in sarcopenia intervention studies. Findings: This scoping review identified 253 distinct outcomes, revealing a high degree of heterogeneity across clinical trials. Muscle mass, muscle strength, and physical performance are the most frequently reported outcomes in sarcopenia trials. Message: A considerable diversity and heterogeneity of reported outcomes were observed in clinical trials, highlighting the urgent need for outcome standardization and the development of a Core Outcome Set specifically for sarcopenia interventions.